Elastic-Plastic stress analysis in the pole fixation of an electric generator. (2022) - Rusu-Casandra, Aurelia; Baciu, Florin; Pastrama, Stefan Dan; Iliescu, Nicolae
Abstract: Hydroelectric power plants are currently the most efficient large scale electric energy producers. Therefore, there are many opportunities for construction of new hydroelectric power plants throughout the world, which makes the study and design of improved electric power generators a priority. The core equipment of an electric power plant is the electric power generator, which can deliver hundreds of MW of electric power, while withstanding high levels of mechanical and thermal stresses under high rotation speeds. Therefore, the design of the electric generator, especially the rotor component, must ensure structural integrity, safety of operation, and an extended lifetime of 30–40 years. To achieve the safe and reliable operation of the generator, one of its components that must be designed after a detailed and comprehensive stress analysis is the rotor pole fixation. When the hydroelectric generator operates under high stress conditions, due to frequent start-stop cycles, structural elements such as the rotor poles fixations could operate beyond their endurance limit and could be exposed to the risk of failure. This paper presents an elastic–plastic finite element analysis of the mechanical response of the pole fixation, part of an assembly with three hammerheads of a hydroelectric generator rotor, under various loading conditions. The elastic–plastic stress analysis leads to a safe design at much higher operational loads compared to a linear elastic analysis and may be further used to study the effect of crack appearance in the plastic zone, preventing a catastrophic failure of the generator.